The Validity of the Alcohol, Smoking and Substance Involvement Screening Test in Patients with Psychotic Disorders - Adlard, Rosalind (Department of Psychiatry and Mental Health, 2022)
Background Given the high prevalence of substance use disorders among patients with persistent mental illnesses, with resultant negative health consequences, a brief and easily administered screening test is needed in this population to identify those at risk in order to intervene appropriately. The Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) was developed by the World Health Organisation as a screening instrument. It has been validated in a variety of settings, including in primary care and treatment settings and in first episode psychosis. Aim To determine the validity and reliability of the ASSIST in detecting substance use disorders in patients with multi-episode psychotic disorders. Setting Western Cape, South Africa. Methods The Structured Clinical Interview for DSM-IV Axis I Disorders was used as the gold standard for detecting DSM-IV substance abuse and dependence. Cronbach's alpha was used to determine the internal consistency of the ASSIST, and receiver operating characteristic analysis was used to evaluate its screening properties. Optimal cut off scores were calculated to maximize sensitivity and specificity. Results A total substance involvement lifetime score of 13 was found to have both sensitivity and specificity of just over 74%. A specific substance involvement score of 4 for alcohol and 3 for cannabis, methamphetamine and ‘other drugs' was found to have optimal balance between sensitivity and specificity. Conclusion The ASSIST is a psychometrically valid screening test for substance use disorders in general, as well as for alcohol, cannabis and methamphetamine use disorders, in patients with multi-episode psychotic disorders.